Aetiology and effective pharmacotherapy of acute bronchitis - A. A. Zaytsev; S. P. Kazakov; E. A. Filon; S. B. Putkov; N. B. Esaulenko (Лечащий Врач)
Objective. To clarify the current etiology of acute bronchitis and to evaluate the possibilities of mucoactive therapy of patients using erdosteine in comparison with real clinical practice, to determine the optimal duration of mucolytic prescription.Materials and methods. A comprehensive study of 60 patients with acute bronchitis, 30 of whom (the first group) received erdosteine, in the second group other mucolytics were used (real clinical practice). The following were evaluated: mean time of cough regression on the background of treatment, duration of mucoactive therapy, terms of relief of all symptoms of acute bronchitis (using BSS scale). Virological and microbiological examination of sputum was performed in 35 patients.Results. Analysis of the main pathogens of acute bronchitis showed that adenovirus infection was registered in 60% of patients, one case each of bocavirus, parainfluenza 1/3 types and rhinovirus infections (2.9% each) were detected. DNA of Chlamydophila pneumonia and Mycoplasma pneumoniae were detected in 48.8% and 17.1% of cases, respectively. It is important that their detection had no effect on the necessity of antimicrobial therapy in patients with acute bronchitis, which confirms the thesis about inexpediency of routine examination for these microorganisms in outpatient practice, except for cases with personalised indications (prolonged course of bronchitis, etc.). The study also updated important indications for antimicrobial therapy in acute bronchitis.Erdosteine has been shown to be highly effective in controlling productive cough in acute bronchitis and to provide optimal duration of treatment. Thus, the duration of erdosteine administration was 5.7 ± 1.4 days, whereas in the control group (other mucolytics) the duration of drug administration was 7.1 ± 1.3 days (p < 0.05).Conclusion. The obtained data expand the knowledge about the etiology of acute bronchitis, pathophysiology of cough in this disease and optimal duration of mucoactive therapy. Appearance of a new mucolytic erdosteine in a doctor's arsenal allows to use it successfully not only in long-term therapy of patients with chronic bronchitis (chronic obstructive pulmonary disease), but also to use it in a whole range of acute situations associated with productive cough (acute bronchitis, pneumonia, exacerbation of bronchiectasis, etc.).